Analisis Aerodinamika pada Sayap JABIRU J430 dengan Penambahan Vortex Generator menggunakan Metode CFD (FTK UNSURYA, 2022)
Jabiru J430 aircraft is a type of light aircraft produced by the Jabiru aircraft manufacturer with four passenger seats which has a length of 6550 mm and a height of 2200 mm with a high wing type with additional winglets. This study aims to determine the effect of installing a vortex generator on the upper surface of the Jabiru J430 aircraft wing on aerodynamic characteristics, especially at critical angle conditions. As it is known that the vortex generator functions to produce a vortex in the air flow on the upper surface of the wing so that it can delay the occurrence of flow separation and improve the performance of the wing. In this study, a comparison was made between the aerodynamic characteristics of the wing without a vortex generator and the addition of a vortex generator. The vortex generator used is a flat plate vortex with a counter-rotating configuration. From the simulation results, it can be seen that the airflow characteristics on the wings using a vortex generator are more stable when compared to airfoils without a vortex generator and it can be seen that the increase in the maximum lift coefficient from CL 0.997 (20 angle of attack) to CL 1.126 (angle of attack 24º) or an increase of 12.9%, and an increase in the drag coefficient occurs as the angle of attack increases.